Prevalence, Cost and Factors Governing Use of Indian Traditional System of Medicines for Anticancer Treatment: Pharmaceutical Science-Pharmacy - K Mathew, Manju; Saravanan. K; Abraham, Sujith (International Journal of Life Science and Pharma Research, 2021)
The Indian traditional system of medicine is a broad set of non-mainstream practices, including use of natural products, for mind as well as body therapies and for the entire medical systems. The aim of this study is to determine the prevalence, costs and factors affecting the usage of ITM. Our methodology is that Demographic data of the participants, cost and factors affecting the ITM of usage were collected. Data were collected from the patients visiting five ITM clinics selected randomly in Kerala, India. The study was conducted between January and December 2020. In the Results of this study, males were predominant (59.72%), age group of 41 to 60 years (51.38%), living in rural parts (73.61%) with school level (61.34%) belongs to the income group of 5001 to 25000 INR per month. 45.19% of patients suffer due to stomach cancer. 16.5 % and 17% of participants were preferred for Ayurvedic and Homeopathic systems of medicines respectively. About 74.07% of the participants informed that they have visited consultants and health care providers. Among the various ITM of medicines, Ayurvedic treatment was higher (35.48%). 10 factors which have decided the use of ITM, out of which, lack of reason to use was major which governed the usage. In Conclusion, the use of ITM is prevalent among participants visiting traditional health clinics in the selected study area. The significant factors observed to improve the possibility of ITM use, was the literate and the place of living. But, factors like age, gender, income and social habits have proved to be key roles to determine the use of the ITM of medicines. Most participants have a strong belief in ITM, due to the concept that ITM can develop immunity systems and has fewer side effects. The present findings suggest that the use of ITM treatment is unlimited to the individual’s chief medical complications. Indian Traditional medical practitioners treating all kinds of medical condition. The present study findings reveal a moderate degree of use of ITM in the selected region of population Kerala, India